Acute cardiac failure secondary to senile systemic amyloidosis. (2nd November 2016) - Bodard, Quentin; Roca, Frederic; Dilly, Baptiste; Laurent, Druesne; Chassagne, Philippe
Abstract: Hereditary or senile transthyretin (TTR) cardiac amyloidosis is a rare and underestimated cause of heart failure in old patients. New diagnostic methods, particularly cardiac MRI and proteomic analysis, have been recently developed that enable both earlier identification and development of specific treatments. We report a case of cardiac amyloidosis revealed through late-onset heart failure.